EVALUATION OF BACTERIAL RESISTANCE OF CEFADROXIL, CEPHALEXIN AGAINST GRAM-POSITIVE AND GRAM-NEGATIVE MICRO-ORGANISMS - SUNDAR, S (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This study was aimed to overcome the problems of bacterial resistance to antibiotics used for the treatment of diseases. Methods: In this aspect, two antibiotics were selected such as cefadroxil and cephalexin for the evaluation of antibiotic resistance against selected three Gram-positive microorganisms such as Bacillus subtilis, Staphylococcus aureus, and Bacillus cereus and three Gram-negative microorganisms such as E. coli, Pseudomonas aeruginosa, and Serratia marcescens. The selected antibiotics were evaluated by the determination of minimum inhibitory concentration and the agar disk diffusion method. Results: According to the results obtained, cefadroxil was resistant against Bacillus cereus (25.6 μg/ml, 10 mm) and Serratia marcescens (25.6, 6 mm), sensitive against Pseudomonas aeruginosa (6.4 μg/ml, 18 mm), Bacillus subtilis (6.4 μg/ml, 30 mm), intermediate against E. coli (12.8 μg/ml, 16 mm), and Staphylococcus aureus (12.8 μg/ml, 15 mm). Similarly, cephalexin was resistant against Serratia marcescens (25.6 μg/ml, 10 mm), intermediate against E. coli (12.8 μg/ml, 14 mm), Pseudomonas aeruginosa (25.6 μg/ml, 14 mm), Bacillus subtilis (12.8 μg/ml, 15 mm), Staphylococcus aureus (6.4 μg/ml, 16 mm), and sensitive against Bacillus cereus (6.4 μg/ml, 18 mm) according to the CLSI report. Conclusion: The increased illness of human beings by the usage of antibiotics frequently without prescriptions is a serious problem that dramatically raises the cost of health-care worldwide. Hence, the study was useful and effective for the determination of antibiotic resistance of cephalexin and cefadroxil for the future treatment in more efficacies with fewer side effects.